Questioning Heroism in Andy Weir’s the Martian - Elisabeth Ngestirosa Endang Woro Kasih; Fajar Dani Julian Tama (Universitas Teknokrat Indonesia, 2023)
The concept of heroism has long been a recurring theme in literature, evolving within American novels to reflect the ever-changing societal values and dynamics. While American novels tend to focus on delineating heroism for multiple characters, the portrayal often feels forced and less authentic in the literary works showcased. This qualitative research aims to explore the evolving portrayal of heroism in contemporary American literature, employing Andy Weir's acclaimed novel, The Martian, as the primary data source. The study meticulously analyzes the depiction of heroism in the story and evaluates its alignment with Joseph Campbell's renowned three-stage theory of the hero's journey. Through the presentation of empowering narratives, the research seeks to encourage readers to recognize heroism in its diverse and multifaceted forms, thereby fostering empathy, understanding, and unity among individuals from varied backgrounds. Ultimately, the findings of the study indicate that heroism in The Martian may not have been presented in the appropriate context, suggesting a potential divergence from conventional portrayals of hero figures. This research opens up intriguing discussions about the portrayal of heroism in modern literature and its implications on our understanding of the human spirit and heroic ideals.